Assessment of Breast Milk Iodine Concentrations in Lactating Women in Western Australia - Jorgensen, Anita; O'Leary, Peter; James, I.; Skeaff, S.; Sherriff, Jill (MDPI Publishing, 2016)
Breast-fed infants may depend solely on an adequate supply of iodine in breast milk for the synthesis of thyroid hormones which are essential for optimal growth and cognitive development. This is the first study to measure breast milk iodine concentration (BMIC) among lactating women in Western Australian (n = 55). Breast milk samples were collected between 2014 and 2015 at a mean (±SD) of 38.5 (±5.5) days post-partum. The samples were analysed to determine median BMIC and the percentage of samples with a BMIC < 100 μg/L, a level considered adequate for breast-fed infants. The influence of (a) iodine-containing supplements and iodised salt use and (b) consumption of key iodine-containing foods on BMIC was also examined. The median (p25, p75) BMIC was 167 (99, 248) μg/L and 26% of samples had a BMIC < 100 μg/L. Overall, BMIC tended to be higher with iodine-containing supplement usage (ratio 1.33, 95% confidence interval (CI) (1.04, 1.70), p = 0.030), cow’s milk consumption (ratio 1.66, 95% CI (1.23, 2.23), p = 0.002) and lower for Caucasians (ratio 0.61, 95% CI (0.45, 0.83), p = 0.002), and those with secondary school only education (ratio 0.66, 95% CI (0.46, 0.96), p = 0.030). For most women, BMIC was adequate to meet the iodine requirements of their breast-fed infants. However, some women may require the use of iodine-containing supplements or iodised salt to increase BMIC to adequate levels for optimal infant nutrition.